(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
This paper characterized the experimental studies published in Brazilian journals in the field of Social Skills Training and identified trends and possible methodological gaps. The 10 experimental studies cited in the study of Bolsoni-Silva et al. (2006) were recovered and a search in the database SCIELO, including the period between 2004 and 2012, was conducted. Studies were carried out with individuals with clinical characteristics, aiming to assess several components of social skills through systematic observation of behavior. The researches have brought contributions to the characterization of the social skills repertoire and social competence of psychotics as well to the verification of the effectiveness of intervention program with university students.